HUBUNGAN MULAI NYERI PERUT DENGAN TINGKAT KEPARAHAN APENDISITIS AKUT ANAK BERDASARKAN KLASIFIKASI CLOUD DI RSUD ARIFIN ACHMAD PROVINSI RIAU - Heru Ardila Putra; Tubagus Odih Rhomdani Wahid; Wiwit Ade Fidiawati (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
Pediatric acute appendicitis is a pediatric surgical cases with the most common presentation was abdominal pain. Abdominal pain in acute appendicitis is the result of inflammation of the appendix. If no immediate appendectomy, it can lead to perforation of the appendix within 24-48 hours after acute inflammation. Pediatric acute appendicitis based on Cloud Classification consists of simple, suppurative, gangrene, rupture and abscess. The aim of this study was to determine the correlation between onset of abdominal pain with severity of peadiatric acute appendicitis based on Cloud Classification. The method of this study was analytical correlative with retrospective cross sectional approach conducted in November 2014. Retrieved 54 medical records of pediatric acute appendicitis patients in surgery department of RSUD Arifin Achmad Riau Province period January 2011 - December 2013. From this study was found that a similar comparison between male and female (1: 1.04), with a mean onset of abdominal pain 3.49 ± 3.29 days before admission to hospital. Based on Cloud Classification was found the severity of pediatric acute appendicitis, ie simple 13.7% , suppurative 29.4%, gangrene 19.6%, rupture 19.6% and abscess 17.6%. Spearman correlative test between onset of abdominal pain with severity of peadiatric acute appendicitis based on Cloud Classification showed p = 0.000 and r = 0.525. The conclusion there was a significant medium correlation between onset of abdominal pain with severity of peadiatric acute appendicitis based on Cloud Classification .Keywords: onset of abdominal pain, pediatric acute apendicitis, Cloud classification